Sentence Fragmentation in the Writing of Senior Secondary School Students of Gwale, Kano, Nigeria - Normah, Yusof; Sharifah Nor Madiah, Syed Omar (2016)
It is conventionally agreed that the effectiveness of written English depends on the grammatical correctness. This study empirically investigated the sentence fragments from the compositions of senior secondary students. It aimed to identify fragments, its frequency and to explore on what causes the fragments. The study employed a mixed method approach in which an embedded design was adopted to guide the collection and analysis of the data. The subjects of the study comprised 30 students purposively selected from secondary schools of Gwale Local Government Area, Kano Nigeria. Achievement Test is used to collect the data. Markin software version 4.222 is used to speed up the process of data analysis. The result of the study revealed that sentence fragments ware frequently found in the participants compositions. Meanwhile, the main causes of fragments were attributed to intra-lingual sources. The study will help teachers to gain insight into the persistent difficulties students are facing in their writing.